Incidencia del plano parental en el rendimiento académico de los estudiantes de la unidad educativa “león de Febres Cordero”, parroquia San Juan, cantón Puebloviejo - Averos Silva, Libia Elena (2017)
The schools in Ecuador and especially in the province of Los Rios, present a deficit in the absence of the parental plane with the education of their children, which are negative effects for society. The study carried out in the "Leon De Febres Cordero" Educational Unit of San Juan CantónPuebloviejo Parish was carried out with the purpose of determining the incidence of the parental plane in the academic performance of the students of the seventh year of basic education. Once the results of the applied surveys were obtained, the analysis and interpretation of the same ones were carried out, being able to understand that in this establishment the object of study, the parents do not give greater importance in the school performance of their children and the effects that they this produces in student learning and behavior, teachers do not have positive strategies to counteract the problem, leaving the formation of the child drifting, it is important that there is a division of responsibility and educational actions between the two institutions that share the time of the child and their possibilities of learning, involving the process of communication between the family and the school. Sharing the educational tasks should be the beginning of the relationship between the family and the school, the results obtained allowed to verify the hypotheses and to conclude that the parental relationship affects the scholastic performance of the student. Given the results, it was considered necessary to propose an alternative proposal with the purpose of achieving the joint participation between teachers, parents and students, with activities that encourage the participation of the father in the school actions of his children and strengthen the teaching-learning process.